2014
DOI: 10.2478/pjvs-2014-0068
|View full text |Cite
|
Sign up to set email alerts
|

Expression of NK1 receptor at the protein and mRNA level in the porcine female reproductive system

Abstract: The presence and distribution of substance P (SP) receptor NK1 was studied in the ovary, the oviduct and the uterus (uterine horn and cervix) of the domestic pig using the methods of molecular biology (RT-PCR and immunoblot) and immunohistochemistry.The expression of NK1 receptor at mRNA level was confirmed with RT-PCR in all the studied parts of the porcine female reproductive system by the presence of 525 bp PCR product and at the protein level by the detection of 46 kDa protein band in immunoblot. Immunohis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…The primers for the RT-PCR assay could be designed based only on the homology of the NK1 receptor mRNA sequences in different mammalian species. For the porcine NK1 receptor, this method enabled the detection of NK1R transcripts only once in the porcine female reproductive system (Bukowski 2014).…”
Section: Oryctolagus Cuniculus Nk2r Sus Scrofa Nk2rmentioning
confidence: 99%
“…The primers for the RT-PCR assay could be designed based only on the homology of the NK1 receptor mRNA sequences in different mammalian species. For the porcine NK1 receptor, this method enabled the detection of NK1R transcripts only once in the porcine female reproductive system (Bukowski 2014).…”
Section: Oryctolagus Cuniculus Nk2r Sus Scrofa Nk2rmentioning
confidence: 99%
“…On the other hand, in pigs, NK1R was expressed at the RNA level not only in the uterus, but also in all parts of the female reproductive system [ 25 ]. The presented study showed the expression of NK1R and NK2R in the myometrium in the physiological state and as a result of inflammation.…”
Section: Discussionmentioning
confidence: 99%